Econometric analysis : re-examining FDI and growth lingkages in Malaysia / Nor Jana Salim, Rajmi Mustaffa and Asma’ Rashidah Idris - Salim, Nor Jana; Mustaffa, Rajmi; Idris, Asma’ Rashidah (Research Management Institute (RMI), 2012)
FDI is perceived to have accelerated economic growth through the financing of domestic investment of developing countries that lack of domestic saving. Malaysia is not left out to rely on FDI to finance domestic investment during the savinginvestment gap recorded the negative values in the 80’s and 90’s. This study aims to re-examine the relationship between FDI and GDP when saving-investment gap has recorded the surplus in the late 90’s. Covering the period from 2000-2010 this study employs Autoregressive Distributed Lag (ARDL) model for integration, the results show all the variables used in the study are co-integrated in the long run. Furthermore, the granger causality test shows a unidirectional causality from FDI to GDP. This can be the evidence that Malaysia still relies on FDI to boost economic growth even though there is a surplus in saving – investment gap.